Evaluation of logistics centres establishment: External and internal factors - Meidutė, Ieva; Raudeliūnienė, Jurgita (Business: Theory and Practice, 2011)
One of the most important research objects in comprehensive theories of strategic management for theoreticians and representatives of logistics is making appropriate competitive strategic decisions and achieving a competitive advantage in dynamic and uncertain business environment. The aim of the topic is to create the conceptual model of evaluation of logistics centres establishment, which allows complex assessment of external and internal factors of competition of logistics centres. The proposed conceptual model of evaluation of logistics centres establishment consists of three main stages: identification of external and internal factors of logistics centre establishment; assessment of external and internal factors; estimation of external and internal factors. Different research methods were applied to reach the aim of the topic: analysis of scientific literature, comparative analysis, systems analysis, methods of conceptual synthesis, multiple criteria assessment, and expert evaluation.